Analisis Lagu "Di Sepertiga Malam" Karya Rey Mbayang Menggunakan Pendekatan Ekspresif - Febby Alizka Putri (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This study analyzes Rey Mbayang's song "Di Sepertiga Malam" using an expressive approach to understand the relationship between the author's emotional and spiritual experiences with the song's lyrics and melody. The research employs a qualitative descriptive method with content analysis, combining data collection from lyrics, interviews, and the author’s biography. The analysis reveals that the lyrics reflect a profound spiritual experience, such as the practice of worship during the last third of the night, conveyed through symbolism and religious messages. The song's dominant soft melody creates a contemplative atmosphere, enhancing its emotional message. The expressive approach reveals that the song mirrors Rey's spiritual journey, serving as a medium to share his religious experiences with listeners. The conclusion highlights that this work not only holds artistic value but also functions as a medium to convey universal spiritual messages.